Afrikaner networks for volksdiens: Stellenbosch volkekundiges, 1926-1997 - (Kees) van der Waal, C.S. (Anthropology Southern Africa, 2022)
Several critical exposés of volkekunde at Stellenbosch University have focused on dominant figures up to the 1960s but have not sufficiently considered how they engaged with Afrikaner nationalism. This article introduces questions around solidarity, discontinuity and dissent amongst volkekundiges up to the closure of their department. The article uses a network approach to unravel how volkekundiges at the university were entangled with Afrikaner organisations and how their work reflected Afrikaner nationalism. Given tightly knit networks at Afrikaans universities and the appearance of monolithic unity, the limited scope for dissent is of interest. The article follows the development of volkekunde at Stellenbosch in tandem with major changes in the apartheid project for which volkekundiges provided theoretical confirmation of the social categories required to divide and rule black people. Three periods (policy development, implementation, and implosion of apartheid) organise the material, illustrating trends towards solidarity of networks but also (minor) disruptions showing differentiation and dissent. Close connections between academic work and ideological support for nationalist politics characterised the rise of volkekunde at Stellenbosch. This trend also led to the abandonment of volkekunde (then "anthropology"), despite last-attempt retooling of an unsustainable tradition during South Africa's democratic transition.